Analyzing the Factors Influencing the Provincial Environmental Quality Index on Java Island, 2017-2021 - Isna Ayu Wulandari; Sitti Retno Faridatussalam (Jurnal Ilmu Manajemen Profitability, 2023)
The Environmental Quality Index serves as an indicator for assessing the efficacy of environmental management and protection. It functions as a reference point for various stakeholders involved in evaluating the performance of environmental preservation efforts. The index's measurement is based on three key indicators: the Water Quality Index, Air Quality Index, and Land Cover Quality Index. This study is conducted with the primary goal of investigating the influence of Population, Human Development Index, Industrial Sector GRDP, and Poverty Level on the Provincial Environmental Quality Index across Java Island during the period of 2017 to 2021. Secondary data is employed for this research, utilizing panel data analysis techniques. The outcomes of this study reveal that the Human Development Index and Poverty Rate significantly impact the Environmental Quality Index. Conversely, the Total Population and Industrial Sector GRDP exhibit no significant influence on the Provincial Environmental Quality Index within Java Island for the years 2017 to 2021.